A equivocada aplicação da responsabilidade tributária de terceiro prevista no artigo 135 do Código Tributário Nacional na dissolução irregular de sociedade - Baena, Luiz Henrique Vano (2019)
The State, in the exercise of the tax jurisdiction, must respect the limitations of tax jurisdiction imposed in the Tax Constitutional System, under penalty of severe violation of constitutional principles. Principles must be understood as the basement of all tax system, which should be harmonically analyzed, relating to each other, for the appropriate operation of the Tax Constitutional System. In the theme approached by this paper, we should note the principle of legal certainty, such as the principles of legality and strict legality, which is why the taxable liability of third parties, under the terms of article 135, must be accurate within the law. The legal norm does not come from the simple reading of legal provisions, and we should not confuse legislative text with legal norm. The legal norm is formed through the construction in the mind of the interpreter. The interpretation of legislation, in order to construct the tax legal norm, cannot exceed the limits brought by the legislator, under penalty of offense to constitutional principles and also the Tax Constitutional System as a whole, that doesn’t allow discretionary application of the law. Unfortunately, even thirty (30) years of Federal Constitution, the public administration has been wrongfully interpreting the article 135 concerning the taxable liability of third parties, in situations that are not foreseen in the law. The expression “personally” mentioned under the main section of the article 135 means that the tax credit will be demanded from the agent who practices the act that generates the tax obligation. Furthermore, the irregular dissolution of the company are not foreseen within the third parties liability referred to in article 135 of Brazilian National Tax Code, that plays no role with the generation of the tributary obligation. That’s a construction created by the Public Administration to satisfy its tax voracity, in profound offence to the constitutional principles that compose the Tax Constitutional System